Current Status of Immunotherapy Treatments for Pancreatic Cancer. Issue 10 (November 2016) - Jimenez-Luna, Cristina; Prados, Jose; Ortiz, Raul; Melguizo, Consolacion; Torres, Carolina; Caba, Octavio
Abstract : Pancreatic cancer (PC) is a lethal disease representing the seventh most frequent cause of death from cancer worldwide. Resistance of pancreatic tumors to current treatments leads to disappointing survival rates, and more specific and effective therapies are urgently needed. In recent years, immunotherapy has been proposed as a promising approach to the treatment of PC, and encouraging results have been published by various preclinical and clinical studies. This review provides an overview of the latest developments in the immunotherapeutic treatment of PC and summarizes the most recent and important clinical trials.